Industrialization and economic diplomacy in Nigeria since 1960: an overview (2012)
The paper examines Nigeria’s economic diplomacy and industrialization efforts since Nigeria’s independence in 1960. It discusses the efforts of all the administrations at foreign relations and the role that Nigeria’s economic resources have played in charting a foreign relations strategy for the country. The work concludes that the quality of leadership that the country has produced over the years has not tied the deployment of Nigeria’s resources globally with her industrialization process. Indeed bureaucratic ineptitude has marred Nigeria’s international economic relations over the years.